Effect of extraction solvents on the content of bioactivecompounds from Larrea tridentata leaves - Martins, Sílvia (2011)
Three organic solvents (methanol, ethanol, and acetone) at four different concentrations (90, 70, 50, and 30% v/v) were used for extraction of hormone-like phenolic compounds (phytoestrogens) from Larrea tridentata leaves, namely, nordihydroguaiaretic acid (NDGA), kaempferol and quercetin. Besides the phytoestrogens extraction the antioxidant potential and the content of total phenols in the produced extracts were also determined. Phytoestrogens recovery varied considerably according to the solvent and concentration used for extraction. The highest NDGA, quercetin and kaempferol contents (46.96 ± 3.39, 10.46 ± 1.01 and 87.00 ± 6.43 mg/g DW plant, respectively) were recovered using 90% (v/v) methanol. All the produced extracts showed antioxidant capacity, but those obtained using 70% and 90% (v/v) methanol had significantly higher (p<0.05) FRAP (ferric reducing antioxidant power) values (2.55 ± 0.09 and 2.73 ± 0.11 mM FE(II)/ g DW plant, respectively) than the remaining ones. These findings allow concluding that 90% (v/v) methanol can be successfully used for the bioactive compounds (phytoestrogens) recovery from Larrea tridentata leaves.